2001
DOI: 10.1080/13682820150217554
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary account of phonological and morphophonological perception in young children with and without otitis media

Abstract: This investigation examined the effects of otitis media with effusion (OME) and its associated fluctuating conductive hearing loss on the perception of phonological and morphophonological /s/ and /z/ in young children. We predicted that children free of OME (OME-) would perform better than children with histories of OME (OME+). We also predicted that for the OME+ group morphological perception would be harder than phonological perception, because the former category carries an additional linguistic load (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
0
19
1
6
Order By: Relevance
“…Petinou et al 16 demonstrated that children aged between 1 and 3 years, diagnosed with hearing loss, show increased language acquisition difficulties, decreased perception of speech sounds containing voiceless or fricative consonants such /s/ and /z/, and frequent phonetic errors when pronouncing /l/ and /r/.17 According to the authors the most common cause is mild conductive hearing loss -which may be unilateral -resulting from otitis media. Paradise18 noted that during these infections sound stimuli are distorted, which could explain the phonetic errors.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Petinou et al 16 demonstrated that children aged between 1 and 3 years, diagnosed with hearing loss, show increased language acquisition difficulties, decreased perception of speech sounds containing voiceless or fricative consonants such /s/ and /z/, and frequent phonetic errors when pronouncing /l/ and /r/.17 According to the authors the most common cause is mild conductive hearing loss -which may be unilateral -resulting from otitis media. Paradise18 noted that during these infections sound stimuli are distorted, which could explain the phonetic errors.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…While some studies show that children with histories of OME have significantly poorer phonological and communication skills than their normally hearing peers [e.g. Miccio et al, 2001;Petinou et al, 2001;Ruben et al, 1997], others did not find any casual relationship between having had episodes of OME and later speech and language development Roberts et al, 1991].…”
mentioning
confidence: 99%
“…Recent examples include studies by research groups in New York City (e.g. Mody and Schwartz, 1999;Petinou, Schwartz, Mody and Gravel, 1999;Petinou, Schwartz, Gravel and Raphael, 2001), State College, PA (e.g. Miccio, Yont, Davie and Vernon-Feagans, 1999;Miccio, Gallagher, Grossman, Yont and Vernon-Feagans, 2001) and Calgary-Montreal (e.g.…”
Section: Descriptive-linguistic Studiesmentioning
confidence: 99%